A Multidisciplinary Approach Integrating Medical, Legal, and Theological Perspectives to Manage Women's Reproduction Health Policy - Lina Nur Anisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This article provides a comprehensive understanding of women's reproductive issues from the perspectives of reproductive health, law, and theology. It highlights how reproductive health is crucial for improving women's quality of life and gender equality while also addressing the challenges in policy implementation. The research uses a qualitative approach, analyzing books, journal articles, and official documents to reveal the positive and negative impacts of assisted reproductive technologies (ART) such as in vitro fertilization (IVF) and intrauterine insemination (IUI) on women's reproductive health. It acknowledges women's reproductive rights in international instruments, yet emphasizes the barriers to their implementation due to social stigma and resource limitations. The study also emphasizes the influence of religious views on public policy and access to reproductive health services. The findings are important for policymakers to create more inclusive and responsive policies for women's reproductive health needs. Additionally, the study highlights the necessity of interfaith dialogue and collaboration between the health, legal, and religious sectors to combat stigma and discrimination surrounding women's reproductive issues. The multidisciplinary approach proposed in this research can serve as a foundation for developing more effective and holistic policies, leading to improved access to and the quality of reproductive health services for women, addressing both their health and rights comprehensively.